The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1177/0271121411425191
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Workshops on Psychological Flexibility for Early Childhood Special Education Staff

Abstract: High stress and burnout are common for early childhood special educators, contributing to high rates of attrition, diminished educational effectiveness, and high turnover. Acceptance and Commitment Therapy (ACT) is a promising approach for the prevention and treatment of a wide variety of problems. Using a randomized wait-list control design, this pilot study evaluated whether ACT workshops delivered to preschool teachers who serve children with developmental disabilities would improve stress-related problems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 76 publications
0
44
0
6
Order By: Relevance
“…There is growing support for using acceptance‐ and mindfulness‐based professional development programs to help teachers address job stress and burnout (Biglan et al., ; Jeffcoat & Hayes, ). The evidence is consistent with studies showing the value of mindfulness‐based interventions, such as Acceptance and Commitment Therapy/Training (ACT), in other organizational settings (Bond & Bunce, , ), as well as research demonstrating ACT's effectiveness with a diverse range of clinical conditions, including anxiety and depression (Bohlmeijer, Fledderus, Rokx, & Pieterse, ; Hayes, Bach, & Boyd, ; Hayes, Boyd, & Sewell, ; Zettle, ; Zettle et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing support for using acceptance‐ and mindfulness‐based professional development programs to help teachers address job stress and burnout (Biglan et al., ; Jeffcoat & Hayes, ). The evidence is consistent with studies showing the value of mindfulness‐based interventions, such as Acceptance and Commitment Therapy/Training (ACT), in other organizational settings (Bond & Bunce, , ), as well as research demonstrating ACT's effectiveness with a diverse range of clinical conditions, including anxiety and depression (Bohlmeijer, Fledderus, Rokx, & Pieterse, ; Hayes, Bach, & Boyd, ; Hayes, Boyd, & Sewell, ; Zettle, ; Zettle et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…We used a 24‐item version of Part B (teacher domain). Biglan et al () utilized data reduction techniques to develop this version and found that decreasing the number of items did not adversely affect reliability. Item responses are on a 7‐point Likert‐type scale and range from 1 ( strongly disagree ) to 6 ( strongly agree ).…”
Section: Methodsmentioning
confidence: 99%
“…Biglan, Layton, Jones, Hankins, and Rusby (2013) found three variables to be associated with SET burnout: experiential avoidance, mindful awareness, and valued living. Experiential avoidance, or an individual's desire to avoid disagreeable situations, thoughts, or feelings, correlated positively with burnout.…”
Section: Individual Level Variables Associated With Burnoutmentioning
confidence: 96%
“…Additional research outcomes have supported the use of ACTraining to mitigate stress levels for university personnel [45 ], early childhood special education teachers [46], and staff members working with individuals diagnosed with intellectual disabilities [47,48]. Mental health workers receiving six ACT-related phone consultations reported improvement in dealing with burnout and a significant progress in personal accomplishment [49].…”
Section: Survey Of the Actraining Researchmentioning
confidence: 99%